PENGUKURAN USER EXPERIENCE (UX) DESAIN APLIKASI TROUBLE TICKET MENGGUNAKAN METODE SUPERGOLDEN RATIO - Gede Ardi Herdiana; Ida Bagus Alit Swarmardika; Rukmi Sari Hartati (Prahasta Publisher, 2022)
The Bali Provincial Information and Statistics Communication Service requires a Trouble Ticket application to report and document internet problems that exist in the offices of the Bali Provincial government. In addition to having functions as needed, the Trouble Ticket application must also pay attention to UI and UX. The method that has been widely used to create UI designs is the Golden Ratio. In addition to the Golden Ratio, there is a Ratio that has not been developed in the field of UI design, the Ratio is the Supergolden Ratio. Supergolden Ratio is the ratio obtained from the Ratio Limit Narayana Sequence which is worth 1.4656. In this study, a Trouble Ticket application design will be designed using the Supergolden Ratio method. The Trouble Ticket and UEQ application designs are given to users to determine the user experience (UX) when using the Trouble Ticket application design. The UEQ results show that the user experience of the application design that is designed using the Supergolden Ratio method produces positive results. Aspects of attractiveness, clarity, efficiency, accuracy, and simulation showed excellent results, while the novelty aspect showed good results.